2005
DOI: 10.2172/878278
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Geochemical Testing of Key Contaminants in Residual Hanford Tank Waste

Abstract: This document was printed on recycled paper.The cover shows a scanning electron microscope image of aluminum (red) and iron (green) in a particle aggregate of residual waste from tank C-106 at the C Tank Farm on the Hanford Site. Cover design by S. B. Neely, Pacific Northwest National Laboratory. SummaryThis report describes the advances that have been made over the past two years in testing and characterizing waste material in Hanford tanks. This waste is being studied because it will remain in the tanks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
1
12
1
Order By: Relevance
“…However, the hexagonal, rod-like dissolution pits observed in some of the U-Na-C-O-P±H residual (post-retrieval) particles (see Figure 3.11) are consistent with the possible prior existence of hexagonal, acicular crystals of čejkaite in this post-retrieval residual sludge. The identification of the possible presence of goethite [α-FeO(OH)], maghemite (γ-Fe 2 O 3 ), and the Na uranates clarkeite Na[(UO 2 )O(OH)](H 2 O) 0-1 ] and/or Na 2 U 2 O 7 in the water-leached pre-retrieval waste from tank C-203 (Deutsch et al , 2005) is generally consistent with the Fe oxide and U-Na phases identified by SEM/EDS in the unleached and leached C-202 and C-203 (post retrieval) residual sludges. The pre-retrieval wastes from tanks C-203 and C-204 also contained a significant fraction of amorphous solids as do the residual waste samples characterized in this study.…”
Section: Comparison Of Sem/eds Results For Residual (Post Retrieval) mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the hexagonal, rod-like dissolution pits observed in some of the U-Na-C-O-P±H residual (post-retrieval) particles (see Figure 3.11) are consistent with the possible prior existence of hexagonal, acicular crystals of čejkaite in this post-retrieval residual sludge. The identification of the possible presence of goethite [α-FeO(OH)], maghemite (γ-Fe 2 O 3 ), and the Na uranates clarkeite Na[(UO 2 )O(OH)](H 2 O) 0-1 ] and/or Na 2 U 2 O 7 in the water-leached pre-retrieval waste from tank C-203 (Deutsch et al , 2005) is generally consistent with the Fe oxide and U-Na phases identified by SEM/EDS in the unleached and leached C-202 and C-203 (post retrieval) residual sludges. The pre-retrieval wastes from tanks C-203 and C-204 also contained a significant fraction of amorphous solids as do the residual waste samples characterized in this study.…”
Section: Comparison Of Sem/eds Results For Residual (Post Retrieval) mentioning
confidence: 99%
“…This creates a significant reduction in the background signal over the key actinide atomic mass range (237-239), resulting in instrument limits of quantification in the range of 7.1 pCi/L for 237 Np and 310 pCi/L for 239 Pu. Successful analysis of fusions from tank C-106 residual sludge material using conventional ICP-MS analysis has been documented by Deutsch et al (2005). However, tank C-106 sludge samples contained nearly three orders of magnitude less uranium than sludge samples from tanks C-202 and C-203.…”
Section: Single Contact Sludge Extraction Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4.3 shows a comparison of the XRD patterns for the 1-month Ca(OH) 2 -and 1-month CaCO 3 -leached samples of C-106 residual waste. Table 4.15 gives a comparison of the XRD and SEM/EDS results for the Ca(OH) 2 -and CaCO 3 -leached samples relative to those from Deutsch et al (2005b) for the C-106 residual waste used as starting material for these leaching tests. Except for the presence of calcite (CaCO 3 ), the phases identified from the XRD patterns for the Ca(OH) 2 -and CaCO 3 -leached samples were also present in the XRD patterns for the C-106 starting material.…”
Section: Xrd Resultsmentioning
confidence: 99%
“…The SEM system is equipped with an Oxford (a) INCA EDS software system that was used for semi-qualitative element analysis. As noted in Deutsch et al (2005b), the JEOL JSM-840 SEM was upgraded in late calendar year 2005 to the Oxford INCA software to automate the collection of EDS spectra over multi-micrometer-size areas of an SEM-imaged sample. This upgrade permits the mapping of the spatial distributions over user-selected areas and/or lines of the relative concentrations of any user-specified element detectable by EDS.…”
Section: Sem/eds Analysismentioning
confidence: 99%